Karakteristik Tegangan Tembus Dielektrik Isolasi Vakum - Tommy Rizky Krisnadi; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The sulfur hexafluorida (SF6) is the best insulators for high voltage. However, SF6 has a very serious problem for the environment that this gas has make a big contribution for global warming. Of course, the study of other insulators is necessary to get the efficient insulation than SF6. Required alternative insulation gases such as carbon dioxide (CO2), nitrogen (N2) or vacuum insulation. From experiment testing with needle electrodes and sphere electrodes for vacuum pressure on -100 mmHg, -150 mmHg, -250 mmHg and -500 mmHg, respectively show the breakdown voltage is lowest than to the air pressure insulation. Then, the data from the study also found that the vacuum breakdown voltage is smaller than air. The use of linear method can show the vacuum breakdown voltage is inversely proportional to the air. But vacuum breakdown voltage is directly proportional to the distance between the needle electrode or sphere electrode.Key words: vacuum insulation, linear method, breakdown voltage